Self-medication: a study on motivational factors and consequences of this practice (Research, Society and Development, 2020)
Self-medication refers to the selection and use of medicines by an individual, without prescription, advice, or monitoring by a qualified health professional, which may cause serious risks and consequences to health, and in some cases, it leads to death. Such practice can occur on its own or even for an indication, and its main purpose is to relieve signs, symptoms, and cure diseases. This habit occurs frequently in our daily lives, not only in Brazil but worldwide. Thus, the present work aims to show how self-medication is frequent and how this practice can harm the health and well-being of the population. This study is a bibliographic review of a qualitative nature, with an exploratory characteristic. Because it is a frequent practice in daily life, the population needs to be aware of the possible risks that self-medication can cause to health, through educational campaigns, lectures and posters. In addition, as it is a recurring theme, it is interesting that studies consider even more deeply the consequences of this practice, such as the difficulties it brings to the treatment against future infections in self-medicating patients.